Mechanisms of force generation and force transmission during interstitial leukocyte migration - Jörg Renkawitz; Michael Sixt (EMBO Reports)
For innate and adaptive immune responses it is essential that inflammatory cells use quick and flexible locomotion strategies. Accordingly, most leukocytes can efficiently infiltrate and traverse almost every physiological or artificial environment. Here, we review how leukocytes might achieve this task mechanistically, and summarize recent findings on the principles of cytoskeletal force generation and transduction at the leading edge of leukocytes. We propose a model in which the cells switch between adhesion-receptor-mediated force transmission and locomotion modes that are based on cellular deformations, but independent of adhesion receptors. This plasticity in migration strategies allows leukocytes to adapt to the geometry and molecular composition of their environment.

﻿﻿Dendritic cell migration across basement membranes in the skin - Pflicke, Holger

Visual discrimination between two sexually deceptive Ophrys species by a bee pollinator - Streinzer, M.; Ellis, Thomas; Paulus, H.; Spaethe, J. (Arthropod-Plant Interactions)
Almost all species of the orchid genus Ophrys are pollinated by sexual deception. The orchids mimic the sex pheromone of receptive female insects, mainly hymenopterans, in order to attract males seeking to copulate. Most Ophrys species have achromatic flowers, but some exhibit a coloured perianth and a bright, conspicuous labellum pattern. We recently showed that the pink perianth of Ophrys heldreichii flowers increases detectability by its pollinator, males of the long-horned bee Eucera berlandi. Here we tested the hypothesis that the bright, complex labellum pattern mimics the female of the pollinator to increase attractiveness toward males. In a dual-choice test we offered E. berlandi males an O. heldreichii flower and a flower from O. dictynnae, which also exhibits a pinkish perianth but no conspicuous labellum pattern. Both flowers were housed in UV-transmitting acrylic glass boxes to exclude olfactory signals. Males significantly preferred O. heldreichii to O. dictynnae flowers. In a second experiment, we replaced the perianth of both flowers with identical artificial perianths made from pink card, so that only the labellum differed between the two flower stimuli. Males then chose between both stimuli at random, suggesting that the presence of a labellum pattern does not affect their choice. Spectral measurements revealed higher colour contrast with the background of the perianth of O. heldreichii compared to O. dictynnae, but no difference in green receptor-specific contrast or brightness. Our results show that male choice is guided by the chromatic contrast of the perianth during the initial flower approach but is not affected by the presence of a labellum pattern. Instead, we hypothesise that the labellum pattern is involved in aversive learning during post-copulatory behaviour and used by the orchid as a strategy to increase outcrossing.

Lipschitz functions have L_p-stable persistence - Cohen-Steiner, David; Herbert Edelsbrunner; Harer, John; Mileyko, Yuriy (Foundations of Computational Mathematics)
We prove two stability results for Lipschitz functions on triangulable, compact metric spaces and consider applications of both to problems in systems biology. Given two functions, the first result is formulated in terms of the Wasserstein distance between their persistence diagrams and the second in terms of their total persistence.

Why is adaptation prevented at ecological margins? New insights from individual-based simulations - Bridle, Jon; Polechova, Jitka; Kawata, Masakado; Butlin, Roger (Ecology Letters)
All species are restricted in their distribution. Currently, ecological models can only explain such limits if patches vary in quality, leading to asymmetrical dispersal, or if genetic variation is too low at the margins for adaptation. However, population genetic models suggest that the increase in genetic variance resulting from dispersal should allow adaptation to almost any ecological gradient. Clearly therefore, these models miss something that prevents evolution in natural populations. We developed an individual-based simulation to explore stochastic effects in these models. At high carrying capacities, our simulations largely agree with deterministic predictions. However, when carrying capacity is low, the population fails to establish for a wide range of parameter values where adaptation was expected from previous models. Stochastic or transient effects appear critical around the boundaries in parameter space between simulation behaviours. Dispersal, gradient steepness, and population density emerge as key factors determining adaptation on an ecological gradient.

Spatial organization of adhesion: force-dependent regulation and function in tissue morphogenesis - Papusheva, Ekaterina; Heisenberg, Carl-Philipp J (EMBO Journal)
Integrin- and cadherin-mediated adhesion is central for cell and tissue morphogenesis, allowing cells and tissues to change shape without loosing integrity. Studies predominantly in cell culture showed that mechanosensation through adhesion structures is achieved by force-mediated modulation of their molecular composition. The specific molecular composition of adhesion sites in turn determines their signalling activity and dynamic reorganization. Here, we will review how adhesion sites respond to mecanical stimuli, and how spatially and temporally regulated signalling from different adhesion sites controls cell migration and tissue morphogenesis.

Planar cell polarity signalling regulates cell adhesion properties in progenitors of the zebrafish laterality organ - Oteíza, Pablo; Koeppen, Mathias; Krieg, Michael; Pulgar, Eduardo; Farias, Cecilia; Melo, Cristina; Preibisch, Steffen; Mueller, Daniel; Tada, Masazumi; Hartel, Steffen; Heisenberg, Carl-Philipp J; Concha, Miguel (Development)
Organ formation requires the precise assembly of progenitor cells into a functional multicellular structure. Mechanical forces probably participate in this process but how they influence organ morphogenesis is still unclear. Here, we show that Wnt11- and Prickle1a-mediated planar cell polarity (PCP) signalling coordinates the formation of the zebrafish ciliated laterality organ (Kupffer's vesicle) by regulating adhesion properties between organ progenitor cells (the dorsal forerunner cells, DFCs). Combined inhibition of Wnt11 and Prickle1a reduces DFC cell-cell adhesion and impairs their compaction and arrangement during vesicle lumen formation. This leads to the formation of a mis-shapen vesicle with small fragmented lumina and shortened cilia, resulting in severely impaired organ function and, as a consequence, randomised laterality of both molecular and visceral asymmetries. Our results reveal a novel role for PCP-dependent cell adhesion in coordinating the supracellular organisation of progenitor cells during vertebrate laterality organ formation.

A role for Rho GTPases and cell-cell adhesion in single-cell motility in vivo - Kardash, Elena; Reichman-Fried, Michal; Maître, Jean-Léon; Boldajipour, Bijan; Ekaterina Papusheva; Messerschmidt, Esther-Maria; Heisenberg, Carl-Philipp; Raz, Erez (Nature Cell Biology)
Cell migration is central to embryonic development, homeostasis and disease(1), processes in which cells move as part of a group or individually. Whereas the mechanisms controlling single-cell migration in vitro are relatively well understood(2-4), less is known about the mechanisms promoting the motility of individual cells in vivo. In particular, it is not clear how cells that form blebs in their migration use those protrusions to bring about movement in the context of the three-dimensional cellular environment(5,6). Here we show that the motility of chemokine-guided germ cells within the zebrafish embryo requires the function of the small Rho GTPases Rac1 and RhoA, as well as E-cadherin-mediated cell-cell adhesion. Using fluorescence resonance energy transfer we demonstrate that Rac1 and RhoA are activated in the cell front. At this location, Rac1 is responsible for the formation of actin-rich structures, and RhoA promotes retrograde actin flow. We propose that these actin-rich structures undergoing retrograde flow are essential for the generation of E-cadherin-mediated traction forces between the germ cells and the surrounding tissue and are therefore crucial for cell motility in vivo.

Movement directionality in collective migration of germ layer progenitors - Arboleda Estudillo, Yohanna; Krieg, Michael; Stuehmer, Jan; Licata, Nicholas; Mueller, Daniel; Heisenberg, Carl-Philipp J (Current Biology)
Collective cell migration, the simultaneous movement of multiple cells that are connected by cell-cell adhesion, is ubiquitous in development, tissue repair, and tumor metastasis [1, 2]. It has been hypothesized that the directionality of cell movement during collective migration emerges as a collective property [3, 4]. Here we determine how movement directionality is established in collective mesendoderm migration during zebrafish gastrulation. By interfering with two key features of collective migration, (1) having neighboring cells and (2) adhering to them, we show that individual mesendoderm cells are capable of normal directed migration when moving as single cells but require cell-cell adhesion to participate in coordinated and directed migration when moving as part of a group. We conclude that movement directionality is not a de novo collective property of mesendoderm cells but rather a property of single mesendoderm cells that requires cell-cell adhesion during collective migration.

A new model for evolution in a spatial continuum - Barton, Nicholas H; Etheridge, Alison; Véber, Amandine (Electronic Journal of Probability)
We investigate a new model for populations evolving in a spatial continuum. This model can be thought of as a spatial version of the Lambda-Fleming-Viot process. It explicitly incorporates both small scale reproduction events and large scale extinction-recolonisation events. The lineages ancestral to a sample from a population evolving according to this model can be described in terms of a spatial version of the Lambda-coalescent. Using a technique of Evans (1997), we prove existence and uniqueness in law for the model. We then investigate the asymptotic behaviour of the genealogy of a finite number of individuals sampled uniformly at random (or more generally `far enough apart') from a two-dimensional torus of sidelength L as L tends to infinity. Under appropriate conditions (and on a suitable timescale) we can obtain as limiting genealogical processes a Kingman coalescent, a more general Lambda-coalescent or a system of coalescing Brownian motions (with a non-local coalescence mechanism).

Ist Bibliothek 2.0 überhaupt noch relevant? – Eine Einleitung in das Handbuch - Bergmann, Julia; Danowski, Patrick (Handbuch Bibliothek 2.0)
Mit diesem Buch möchten wir einen Überblick der aktuellen Diskussion zum Thema Bibliothek 2.0 geben und den Stand der tatsächlichen Umsetzung der Web 2.0-Ansätze in deutschsprachigen Bibliotheken beleuchten. An dieser Stelle ist die Frage erlaubt, warum es zu einer Zeit, in der es bereits die ersten "Web 3.0"- Konferenzen gibt, eines Handbuches der Bibliothek 2.0 noch bedarf. Und warum es überhaupt ein deutschsprachiges Handbuch zur Bibliothek 2.0 braucht, wo es doch bereits verschiedenste Publikationen zu diesem Thema aus anderen Ländern, insbesondere des angloamerikanischen Raums gibt. Ist dazu nicht bereits alles gesagt?

Open bibliographic data - Danowski, Patrick (European Library Automation Group (ELAG) 2010)
More and more libraries starting semantic web projects. The question about the license of the data is not discussed or the discussion is deferred to the end of project. in this paper is discussed why the question of the license is so important in context of the semantic web that is should be one of the first aspects in a semantic web project. Also it will be shown why a public domain weaver is the only solution that fulfill the the special requirements of the semantic web and that guaranties the reuseablitly of semantic library data for a sustainability of the projects.

Step one: blow up the silo! - Open bibliographic data, the first step towards Linked Open Data - Patrick Danowski
More and more libraries starting semantic web projects. The question about the license of the data is not discussed or the discussion is deferred to the end of project. in this paper is discussed why the question of the license is so important in context of the semantic web that is should be one of the first aspects in a semantic web project. Also it will be shown why a public domain weaver is the only solution that fulfill the the special requirements of the semantic web and that guaranties the reuseablitly of semantic library data for a sustainability of the projects.

Handbuch Bibliothek 2.0
With the term "Library 2.0" the editors mean an institution which applies the principles of the Web 2.0 such as openness, re-use, collaboration and interaction in the entire organization. Libraries are extending their service offerings and work processes to include the potential of Web 2.0 technologies. This changes the job description and self-image of librarians. The collective volume offers a complete overview of the topic Library 2.0 and the current state of developments from a technological, sociological, information theoretical and practice-oriented perspective.

Evolutionary genomics of Staphylococcus aureus reveals insights into the origin and molecular basis of ruminant host adaptation - Guinane, Caitriona M; Ben Zakour, Nouri L; Tormo-Mas, Maria A; Weinert, Lucy A; Lowder, Bethan V; Cartwright, Robyn A; Smyth, Davida S; Smyth, Cyril J; Lindsay, Jodi A; Gould, Katherine A; Witney, Adam; Hinds, Jason; et al. (Genome Biology and Evolution)
Phenotypic biotyping has traditionally been used to differentiate bacteria occupying distinct ecological niches such as host species. For example, the capacity of Staphylococcus aureus from sheep to coagulate ruminant plasma, reported over 60 years ago, led to the description of small ruminant and bovine S. aureus ecovars. The great majority of small ruminant isolates are represented by a single, widespread clonal complex (CC133) of S. aureus, but its evolutionary origin and the molecular basis for its host tropism remain unknown. Here, we provide evidence that the CC133 clone evolved as the result of a human to ruminant host jump followed by adaptive genome diversification. Comparative whole-genome sequencing revealed molecular evidence for host adaptation including gene decay and diversification of proteins involved in host-pathogen interactions. Importantly, several novel mobile genetic elements encoding virulence proteins with attenuated or enhanced activity in ruminants were widely distributed in CC133 isolates, suggesting a key role in its host-specific interactions. To investigate this further, we examined the activity of a novel staphylococcal pathogenicity island (SaPIov2) found in the great majority of CC133 isolates which encodes a variant of the chromosomally encoded von Willebrand-binding protein (vWbp(Sov2)), previously demonstrated to have coagulase activity for human plasma. Remarkably, we discovered that SaPIov2 confers the ability to coagulate ruminant plasma suggesting an important role in ruminant disease pathogenesis and revealing the origin of a defining phenotype of the classical S. aureus biotyping scheme. Taken together, these data provide broad new insights into the origin and molecular basis of S. aureus ruminant host specificity.

Forward analysis of depth-bounded processes - Wies, Thomas; Zufferey, Damien; Henzinger, Thomas A
Depth-bounded processes form the most expressive known fragment of the π-calculus for which interesting verification problems are still decidable. In this paper we develop an adequate domain of limits for the well-structured transition systems that are induced by depth-bounded processes. An immediate consequence of our result is that there exists a forward algorithm that decides the covering problem for this class. Unlike backward algorithms, the forward algorithm terminates even if the depth of the process is not known a priori. More importantly, our result suggests a whole spectrum of forward algorithms that enable the effective verification of a large class of mobile systems.

Runtime verification for software transactional memories - Singh, Vasu
Software transactional memories (STMs) promise simple and efficient concurrent programming. Several correctness properties have been proposed for STMs. Based on a bounded conflict graph algorithm for verifying correctness of STMs, we develop TRACER, a tool for runtime verification of STM implementations. The novelty of TRACER lies in the way it combines coarse and precise runtime analyses to guarantee sound and complete verification in an efficient manner. We implement TRACER in the TL2 STM implementation. We evaluate the performance of TRACER on STAMP benchmarks. While a precise runtime verification technique based on conflict graphs results in an average slowdown of 60x, the two-level approach of TRACER performs complete verification with an average slowdown of around 25x across different benchmarks.

Counterexample-guided focus - Podelski,Andreas; Thomas Wies

From MTL to deterministic timed automata - Nickovic, Dejan; Piterman, Nir
In this paper we propose a novel technique for constructing timed automata from properties expressed in the logic mtl, under bounded-variability assumptions. We handle full mtl and include all future operators. Our construction is based on separation of the continuous time monitoring of the input sequence and discrete predictions regarding the future. The separation of the continuous from the discrete allows us to determinize our automata in an exponential construction that does not increase the number of clocks. This leads to a doubly exponential construction from mtl to deterministic timed automata, compared with triply exponential using existing approaches. We offer an alternative to the existing approach to linear real-time model checking, which has never been implemented. It further offers a unified framework for model checking, runtime monitoring, and synthesis, in an approach that can reuse tools, implementations, and insights from the discrete setting.

Building a calculus of data structures - Kuncak, Viktor; Piskac, Ruzica; Suter, Philippe; Wies, Thomas
Techniques such as verification condition generation, predicate abstraction, and expressive type systems reduce software verification to proving formulas in expressive logics. Programs and their specifications often make use of data structures such as sets, multisets, algebraic data types, or graphs. Consequently, formulas generated from verification also involve such data structures. To automate the proofs of such formulas we propose a logic (a “calculus”) of such data structures. We build the calculus by starting from decidable logics of individual data structures, and connecting them through functions and sets, in ways that go beyond the frameworks such as Nelson-Oppen. The result are new decidable logics that can simultaneously specify properties of different kinds of data structures and overcome the limitations of the individual logics. Several of our decidable logics include abstraction functions that map a data structure into its more abstract view (a tree into a multiset, a multiset into a set), into a numerical quantity (the size or the height), or into the truth value of a candidate data structure invariant (sortedness, or the heap property). For algebraic data types, we identify an asymptotic many-to-one condition on the abstraction function that guarantees the existence of a decision procedure. In addition to the combination based on abstraction functions, we can combine multiple data structure theories if they all reduce to the same data structure logic. As an instance of this approach, we describe a decidable logic whose formulas are propositional combinations of formulas in: weak monadic second-order logic of two successors, two-variable logic with counting, multiset algebra with Presburger arithmetic, the Bernays-Schönfinkel-Ramsey class of first-order logic, and the logic of algebraic data types with the set content function. The subformulas in this combination can share common variables that refer to sets of objects along with the common set algebra operations. Such sound and complete combination is possible because the relations on sets definable in the component logics are all expressible in Boolean Algebra with Presburger Arithmetic. Presburger arithmetic and its new extensions play an important role in our decidability results. In several cases, when we combine logics that belong to NP, we can prove the satisfiability for the combined logic is still in NP.